2017
DOI: 10.1007/s00392-017-1164-4
|View full text |Cite
|
Sign up to set email alerts
|

The T-peak-to-T-end interval: a novel ECG marker for ventricular arrhythmia and appropriate ICD therapy in patients with hypertrophic cardiomyopathy

Abstract: A prolonged TpTe is associated with VA and AT in HCM. Our findings suggest that TpTe can possibly serve as a marker for ventricular arrhythmogenesis in pts. with HCM and assessment of TpTe might, therefore, optimize SCD risk stratification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 31 publications
0
7
0
1
Order By: Relevance
“…As a result, CKD and RRT can cause electrical abnormalities in the heart, frequently leading to fatal arrhythmia. In addition, increased blood pressure and volume load in CKD patients may also contribute to a background of mechanical and electrical imbalances in myocytes, thereby increasing the likelihood of ventricular tachycardia [ 22 , 23 , 24 ]. Therefore, CKD patients may have a higher probability of cardiac arrest than non-CKD patients because of the high risk of fatal arrhythmia.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, CKD and RRT can cause electrical abnormalities in the heart, frequently leading to fatal arrhythmia. In addition, increased blood pressure and volume load in CKD patients may also contribute to a background of mechanical and electrical imbalances in myocytes, thereby increasing the likelihood of ventricular tachycardia [ 22 , 23 , 24 ]. Therefore, CKD patients may have a higher probability of cardiac arrest than non-CKD patients because of the high risk of fatal arrhythmia.…”
Section: Discussionmentioning
confidence: 99%
“…T-peak to T-end interval is depicted as an index for transmural dispersion of ventricular repolarization. Any prolongation in this interval has been considered as a risk factor for ventricular tachyarrhythmia (Dinshaw et al, 2018;Tse et al, 2018). A Turkish study determined that heart rate was significantly higher and maximum P wave duration and P wave dispersion were significantly longer in patients with iron deficiency anemia when compared to healthy controls (Simsek et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Hence, in patients with leprosy, in addition toQT and QTc prolongation, LAH that occurs at high rates is also an important ECG finding that should be considered, and it is highly important to monitor the QT and QTc intervals on ECG to predict arrhythmic events in these patients. On the other hand, recent studies showed that prolongation of the Tp-e interval is a marker of ventricular arrhythmias, increased risk of mortality in congenital long QT syndromes, hypertrophic cardiomyopathy, and also in patients with myocardial infarction who underwent primary percutaneous coronary intervention (18)(19)(20)(21). Prolongation of the Tp-e interval indicates a period of potential vulnerability to reentrant ventricular arrhythmias (22).…”
Section: Discussionmentioning
confidence: 99%